IRF3 contributes to sepsis pathogenesis in the mouse cecal ligation and puncture model - Walker, Wendy E. (Society for Leukocyte Biology, 2012)
Much remains to be learned regarding which components of the innate immune response are protective versus detrimental during sepsis. Prior reports demonstrated that TLR9 and MyD88 play key roles in the CLP mouse model of sepsis; however, the role of additional PRRs and their signaling intermediates remains to be explored. In a prior report, we demonstrated that the signal adaptor IRF3 contributes to the systemic inflammatory response to liposome:DNA. We hypothesized that IRF3 might likewise promote sepsis in the CLP model. Here, we present results demonstrating that IRF3-KO mice have reduced disease score, mortality, hypothermia, and bacterial load following CLP versus WT counterparts. This is paired with reduced levels of systemic inflammatory mediators in IRF3-KO mice that undergo CLP. We demonstrate that peritoneal cells from WT CLP mice produce more cytokines than IRF3-KO counterparts on a per-cell basis; however, there are more cells in the peritoneum of IRF3-KO CLP mice. Finally, we show that IRF3 is activated in macrophages cultured with live or sonicated commensal bacteria. These results demonstrate that IRF3 plays a detrimental role in this mouse model of sepsis.